Visible‐Light Cascade Photooxygenation of Tetrahydrocarbazoles and Cyclohepta[b]indoles: Access to C, N‐Diacyliminium Ions. Issue 30 (23rd June 2020) - Frahm, Mario; von Drathen, Thorsten; Gronbach, Lisa Marie; Voss, Alice; Lorenz, Felix; Bresien, Jonas; Villinger, Alexander; Hoffmann, Frank; Brasholz, Malte
Abstract: Tetrahydrocarbazoles and perhydrocyclohepta[b]indoles undergo a catalytic cascade singlet oxygenation in alkaline medium, which leads to chiral tricyclic perhydropyrido‐ and perhydroazepino[1, 2‐a]indoles in a single operation. These photooxygenation products are new synthetic equivalents of uncommon C, N‐diacyliminium ions and can be functionalized with the aid of phosphoric acid organocatalysis. Abstract : Splashing down the ponds : The cascade photooxygenation of tetrahydrocarbazoles and cyclohepta[ b ]indoles leads to chiral tricyclic perhydropyrido‐ and perhydroazepino[1, 2‐ a ]indoles, which are precursors to uncommon C, N ‐diacyliminium ions.